Landscape Drawing and Comprehension: the Virtuous Passage of Scale in Digital Representation (diségno, 2019)
The latest developments in digital representation and communication of architectural and environmental heritage offer an extremely diverse range of opportunities in which to experiment and implement new models of user involvement in cognitive paths. The study proposed here investigates –according to a methodology of critical reading– which are the aspects that can be considered most innovative, not only in terms of formal results but above all in terms of contents that can be expressed as a result of the use of new technologies.In particular, reference is made to the landscape drawing and to the possibility of overcoming the scale representation gap of a subject who, otherwise, is significantly affected by the limit dictated by the finite nature (or finite dimension) of paper supports. New figurative models –if you think of satellite navigators– new possibilities of relationship between different forms of expression –think about photography and synthetic design– also change the figure of the possible users of such visual narratives.The aim of the study is therefore to arrive at a critical reading of what happens in the context of landscape representation in order to optimize the possibility of introducing unpublished scenarios and points of view.
Keywords: landscape; representation; method; communication